Profilometry and atomic force microscopy for surface characterization - Li Mei; Guangzhao Guan (Nano TransMed)
ABSTRACT: Aim: This study aims to evaluate and compare the profilometry and atomic force microscopy (AFM) for characterization of biomaterial surfaces. Method: The clinically commonly used titanium (Ti) was used as the specimen. Each of the specimen was prepared by different grits of sandpapers, including 2000, 1000, 800, 600, 400, 220, 180, and 100 grits. An unpolished Ti plate served as the control. Surface characterization of the Ti specimens was examined using profilometry and AFM. Results: Both profilometry and AFM were capable of producing two-dimensional (2D) and three-dimensional (3D) topography. The scanning speed of profilometry (12 ± 5 s/image) was faster than that of AFM (250 ± 50 s/image) (p < 0.01). The resolution of AFM was relatively higher than profilometry. AFM produced more precise value, especially at nano-scale. When the Ti surface roughness was less than 0.2 μm, the results of surface roughness measured by profilometry and AFM were similar (mean difference = 0.01 ± 0.03, p = 0.81). When the Ti surface μm, the surface roughness measured by profilometry was slightly higher than that by AFM (mean difference = 0.43 ± 0.15, p = 0.04). Conclusion: Profilometry and AFM are both useful techniques for the characterization of biomaterial surfaces. Profilometry scanned faster than the AFM but produced less detailed surface topography. Both technologies provided similar measurement when the roughness was less than 0.2 μm. When the Ti surface roughness was more than 0.3 μm, the surface roughness measured by profilometry was slightly higher than that by AFM.